Modelling a System to Help Improve It; Comment on "Insights Gained From a Re-analysis of Five Improvement Cases in Healthcare Integrating System Dynamics Into Action Research" - John Øvretveit (Kerman University of Medical Sciences, 2023)
The article that this commentary considers describes the use of systems modelling in an action research (AR) project that helped improvement teams to understand the dynamics of their service as a system. This commentary seeks to make the complex article easier to understand for those unfamiliar with the subjects. It describes the advantages, disadvantages and benefits, and suggests developments of this approach for research and practice using digital technologies. The conclusion of the commentary is that dynamic system modelling combined with AR is useful for certain purposes and can produce benefits in terms of a more sophisticated understanding of systems and feedback loops for practitioners. However, there are challenges for researchers unfamiliar with AR and dynamic system modelling as well workshop facilitation expertise.